SEMIOTIKA RUANG SEBAGAI UNSUR PEMBENTUK STRUKTUR PERMUKIMAN TRADISIONAL BALUWARTI DI KERATON SURAKARTA - , RR. SOPHIA RATNA HARYATI; , Dr. Ir. Laretna Trisnantari Adhisakti, M.Arch ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Settlement Baluwarti as traditional royal heritage historic village (historical urban centers), contained within the walls of the fortress palace of Surakarta is a traditional form of settlement is still actively populated and possess historical background, physical form (artifacts), and activities typical. As time goes by and the demands and system life, Baluwarti has undergone phase change from time to time, which appears on occupancy, facilities and infrastructure, as well as the various elements or elements forming the structure Baluwarti environment in the past and in the present. Notice any symptoms of the area changes, it becomes an important thing to be found is related to the settlement structure seen from the study of spatial semiotics. The purpose of this study is to find the elements of urban design and the changes that have semiotic value of valuable historical meaning signs yet of change as a structure - forming settlements in Baluwarti useful for the preparation of directives or guidelines in handling regional development Baluwarti. This study included exploratory research into the area, as is expected to see a change or degradation of the region from the perspective of the meaning of signs (semiotics) that make up the faÃ§ade and identity Baluwarti region. This study uses qualitative research rationalist models, with an approach that departs from the theoretical construct, then compiled the foundation of his theory of substance literature review, which is then used to guide the research step. The results of the study semiotics Baluwarti forming region of space this will be the basis for the management and structuring of the area as a form of settlement tradisioanal Baluwarti which have a specific arrangement and requires the handling of detail in the arrangement of the building and its environment, to support the potential of preserving the history and heritage artifacts the culture, in order to remain sustainable (non-bleeding) facing the changing times there.